The Epstein-Barr Virus (EBV) in T Cell and NK Cell Lymphomas: Time for a Reassessment - Gru, A. A. (Curr Hematol Malig Rep, 2015)
While Epstein-Barr virus (EBV) was initially discovered and characterized as an oncogenic virus in B cell neoplasms, it also plays a complex and multifaceted role in T/NK cell lymphomas. In B cell lymphomas, EBV-encoded proteins have been shown to directly promote immortalization and proliferation through stimulation of the NF-κB pathway and increased expression of anti-apoptotic genes. In the context of mature T/NK lymphomas (MTNKL), with the possible exception on extranodal NK/T cell lymphoma (ENKTL), the virus likely plays a more diverse and nuanced role. EBV has been shown to shape the tumor microenvironment by promoting Th2-skewed T cell responses and by increasing the expression of the immune checkpoint ligand PD-L1. The type of cell infected, the amount of plasma EBV DNA, and the degree of viral lytic replication have all been proposed to have prognostic value in T/NK cell lymphomas. Latency patterns of EBV infection have been defined using EBV-infected B cell models and have not been definitively established in T/NK cell lymphomas. Identifying the expression profile of EBV lytic proteins could allow for individualized therapy with the use of antiviral medications. More work needs to be done to determine whether EBV-associated MTNKL have distinct biological and clinical features, which can be leveraged for risk stratification, disease monitoring, and therapeutic purposes.